Komodifikasi Agama: Pergeseran Praktik Bisnis dan Kemunculan Kelas Menengah Muslim - Asmaul Husna (Jurnal Komunikasi Global, 2018)
In recent years the Islamic consumption trend has spread throughout the country. At first glance, this phenomenon seems encouraging, because physically the condition seems to describe an increase in religiosity in the midst of the society in an effort to fulfill their spiritual needs. But in other perspectives, actually, this phenomenon has created influence and emerged other interests. The euphoria of religious identity actualization, used by business people to make it as a commodity which is then used as a selling tool. Business and marketing practices are currently shifting and experiencing transformation, from level of rational intelligence (marketing 1.0) to emotional marketing (marketing 2.0) and ultimately to the level of spiritual intelligence (marketing 3.0). Using a literature study method, this article seeks to reveal how such business practices of religious commodification have a real impact on the shift in consumer understanding of their religious identity. The rise of Islamic culture in the midst of this public space also raised a new market segmentation known as the middle-class Muslim. As a consequence, the differences of religiosity and business becomes blurred; religious practices begin to be trapped in the symbolic framework which only prioritizes camouflage and mere imaging.